Effects of an 8-week high-intensity exercise program on anxiety and academic performance in high school students - Pastén Hernández, Pablo; De Souza Lima, Josivaldo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
This study aimed to evaluate the effects of an 8-week high-intensity exercise program on anxiety and academic performance in high school students. A total of 37 participants were recruited, and were randomly assigned to the control group n19 (51.4%) and the experimental group n18 (48.6%). They presented adherence to the program (98%). The intensity was aimed at 80% to 95% of the frequency maximum heart rate, with sessions of 10 minutes with a frequency of 3 times a week. The intensity of the exercise was measured through the Borg perception of exertion scale. Beck’s anxiety inventory validated in the Chilean population was used to measure state anxiety and the school’s official grades record (Papinotas) was used to measure academic performance in language and mathematics. The post-intervention experimental group showed a decrease in anxiety from 22.2±11.99 to 13.7±8.19, in language the average grade increased from 4.61±0.97 to 5.12±0.90 in mathematics no significant results were found. An 8-week high-intensity exercise program was shown to decrease anxiety symptoms and improve language academic performance in high school students in a convenience sample.